2012
DOI: 10.1007/s11356-012-0811-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Bacillus cereus IST105 from electroplating effluent for detoxification of hexavalent chromium

Abstract: Isolated strain B. cereus was able to remove and detoxify chromium (VI). It would be an efficient tool of the biotechnological approach in mitigating the heavy metal pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…MC1 cells by SEM; EDX showed the presence of Cr peak in exposed cells, but it is absent in unexposed control cells. Likewise, Naik, Srivastava, and Thakur (2012) reported morphological changes in treated B. cereus cells (small, round-shaped with uneven edges on the cell wall), and there was a peak of chromium observed in EDX. They asserted that the change in cell shape due to heavy metal exposure is an adopted mechanism to resist the toxicity of heavy metals.…”
Section: Sem-eds Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…MC1 cells by SEM; EDX showed the presence of Cr peak in exposed cells, but it is absent in unexposed control cells. Likewise, Naik, Srivastava, and Thakur (2012) reported morphological changes in treated B. cereus cells (small, round-shaped with uneven edges on the cell wall), and there was a peak of chromium observed in EDX. They asserted that the change in cell shape due to heavy metal exposure is an adopted mechanism to resist the toxicity of heavy metals.…”
Section: Sem-eds Analysismentioning
confidence: 80%
“…In our study, the functional groups such as hydroxyl, phosphate, and amide might be responsible for absorption of reduced Cr 3C in the form of Cr (OH) 3 or CrPO 4 . Naik, Srivastava, and Thakur (2012) also reported the role of carboxyl, phosphate, and amide groups for the absorption of chromium.…”
mentioning
confidence: 99%
“…The process was carried out according to [18]. Energy dispersive X-ray analysis (EDAX, USA) was done in order to confirm the role of cyanobacterial EPS in metal chelation.…”
Section: Scanning Electron Microscope and Energy Dispersive X-ray (Sementioning
confidence: 99%
“…This might be due to the over production of exopolysaccharide (EPS) by the bacterial cells which is one of the mechanism used to resist the metal ions toxicity. Naik et al [6] indicated that B. cereus which has high ability to tolerate Cr 3+ exhibited more than 75 % of Cr 3+ removal. Moreover, understand the response of bacterial cells to the environmental factors represent the critical step to find a more suitable bacterial strain with high efficiency to remove heavy metals.…”
Section: Introductionmentioning
confidence: 99%